The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1111/dmcn.13459
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of pain in children and adolescents with cerebral palsy: a retrospective population‐based registry study

Abstract: The distribution of pain between CP subtypes, functional levels, sex, and age in CPUP is concordant with previous population-based studies, indicating the validity of the CPUP pain screening. Despite this, further clinical evaluation with extended pain assessments and pain management were largely neglected in children reporting chronic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
98
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(119 citation statements)
references
References 26 publications
14
98
4
1
Order By: Relevance
“…The pain prevalence (32–49%) depended on recall period and cut‐off value and was similar to previous estimates in children and adolescents with CP . The most common pain sites were similar to previous descriptions . In earlier studies including children and adolescents with CP, the prevalence of pain has been reported as slightly higher in GMFCS‐ER level V but otherwise fairly evenly distributed within GMFCS‐ER levels I to IV .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The pain prevalence (32–49%) depended on recall period and cut‐off value and was similar to previous estimates in children and adolescents with CP . The most common pain sites were similar to previous descriptions . In earlier studies including children and adolescents with CP, the prevalence of pain has been reported as slightly higher in GMFCS‐ER level V but otherwise fairly evenly distributed within GMFCS‐ER levels I to IV .…”
Section: Discussionsupporting
confidence: 88%
“…The Bodily Pain domain in the SF‐36v2 combines prevalence and severity, and the findings show that pain in young adults with CP was reported to a similar extent as in population norms, with only small sex differences. The pain prevalence (32–49%) depended on recall period and cut‐off value and was similar to previous estimates in children and adolescents with CP . The most common pain sites were similar to previous descriptions .…”
Section: Discussionsupporting
confidence: 87%
“…Pain in CP has now been identified as one of the most important factors decreasing participation in daily activities and negatively affecting all aspects of self‐perceived quality of life . The article by Westbom et al . has again identified that pain in individuals with CP is common: 37% in their population‐representative screened sample.…”
mentioning
confidence: 97%
“…Screening and identifying pain is a good start. Westbom et al . have provided evidence that this is possible.…”
mentioning
confidence: 99%
See 1 more Smart Citation